Medicina narrativa e identità personale - Marinelli, Massimiliano (B@belonline, 2021)
Narrative Medicine is a communicative practice that directs care towards the person. In order to deal with the person and not entertain oneself in the safe territory of the sick body, it is necessary to place oneself in the dimension and perspective of those in front of you, placing the patient’s usual world and his order of meaning within the care relationship. It is believed that under the figure of the narrative identity it is possible to indicate the modalities of intersubjective relationship, in which the narrative is able to orient the care towards the person; in fact, narrative identity shows the dynamism of personal identity, the intertwining of stories and the reconfiguration of the self. Through the narration it is possible to express the sense of what the person, put aside by the diagnostic apparatus, would like to say to the doctor and which remains hidden from the discourse on the body. By removing this sort of epochè, the diagnostic and therapeutic process centered on the entity is included in the dialectic between explanation and understanding, in the anthropological territory of the search for a concordance on the plan of care.